Pro-social attitudes towards ethno-religious out-groups during the COVID-19 pandemic: A survey experiment in five countries - Sarah Carol; Lea David; Siniša Malešević; Gordana Uzelac (International Sociology, 2024)
To what extent were individuals willing to help others during the pandemic? This article examines pro-social attitudes among 7000 residents in England, Ireland, Germany, Serbia, and Sweden by showing a fictitious scenario of an older neighbour who needs his groceries to be picked up from a nearby supermarket. The online survey experiment follows a 3 2 2 factorial design varying the ethno-religious origin of neighbours signalled by the name (Alexander vs Mohammed), the length of their residence (<10.167emyear, 100.167emyears, entire life), and if groceries, or groceries and beer need to be collected. We find that those of minority origin and those who have spent less than a year in a country are disadvantaged. Overall, religiosity is associated with a lower willingness to help a neighbour.
Keywords: 300; COVID-19; Europe; minorities; pro-sociality; religion; solidarity